Melacak Jejak Perubahan Sosial dan Dinamika Pemerintahan Kasepuhan Gelar Alam di Era Modernisasi dan Globalisasi - Oktopiani, Leni; Azzahra, Viona; Anisa, Izjtihad; Fariz, Irland; Chandra, Dwi; Fadhlika, Hafez (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to determine the dynamics and social changes that occur in Kasepuhan Gelar Alam due to the penetration of modernization and globalization. This research uses descriptive analysis method with qualitative approach. The data collection techniques used in this research are observation and interviews using informants who fit the criteria in order to obtain reliable data. The results of the research show that the ability to respond to change, the Kasepuhan Gelar Alam community is a community that has high compliance with customary law and traditional values. Although they accept modernization and globalization, they permanently maintain cultural values and customs that have been passed down from generation to generation. Kasepuhan Gelar Alam, being an indigenous community rich in cultural heritage and tradition, can strengthen sustainability and preservation through several strategic steps. Cooperation and coordination between the local government and the community are needed to manage natural resources sustainably, ensuring good planning, appropriate technology utilization, and environmental preservation.